Aortic dimensions by multi-detector computed tomography vs. echocardiography. Issue 4 (April 2016) - Blondheim, David S.; Vassilenko, Lubov; Glick, Yair; Asif, Aya; Nachtigal, Alicia; Meisel, Simcha R.; Shochat, Michael; Shotan, Avraham; Zeina, Abdel-Rauf
Abstract: Objective: Clinical follow-up of aortic dimensions is performed interchangeably by multi-detector computed tomography (MDCT) and by cardiac echocardiography (ECHO). This study assesses the relationship between measurements of the aortic diameter by MDCT and ECHO at various predetermined locations using several methods. Methods: The aortic diameter was measured at 6 locations between the aortic annulus and the aortic arch in 49 patients who underwent both MDCT and ECHO. Measurements were performed by three methods: internal-to-internal edge (INT), external-to-internal edge (MIX), and external-to-external edge (EXT). Measurements by MDCT and ECHO were made by an experienced radiologist and cardiologist, respectively, both blinded to results and images from the other modality. Results: The average aortic diameter at all locations was significantly different between the MDCT and ECHO by all three methods (INT: 30.0 ± 5.8 mm vs. 27.8 ± 5.9 mm; MIX: 31.5 ± 5.8 mm vs. 30.8 ± 5.8 mm; EXT: 32.9 ± 6.6 mm vs. 33.8 ± 6.5 mm, p < 0.002 for all). While mean absolute differences between INT and EXT methods were similar (3.5 ± 3.1 mm and 3.4 ± 2.7 mm, respectively), the absolute difference using the MIX method was significantly smaller (3.1 ± 2.8 mm; p < 0.001 for INT vs. MIX; p < 0.05 for EXT vs. MIX). Conclusions: There is considerable variability between MDCT and ECHO measurements of the ascending aorta. Measuring the aortic diameter by the MIX provides the closest measurements and is advised for long-term follow-up.